Loss of Genome Fidelity: Beta HPVs and the DNA Damage Response - Wendel, Sebastian O.; Wallace, Nicholas A. (Frontiers in Microbiology, 2017)
While the role of genus alpha human papillomaviruses in the tumorigenesis and tumor maintenance of anogenital and oropharyngeal cancers is well-established, the role of genus beta human papilloviruses (β-HPVs) in non-melanoma skin cancers (NMSCs) is less certain. Persistent β-HPV infections cause NMSCs in sun-exposed skin of people with a rare genetic disorder, epidermodysplasia verruciformis. However, β-HPV infections in people without epidermodysplasia verruciformis are typically transient. Further, β-HPV gene expression is not necessary for tumor maintenance in the general population as on average there is fewer than one copy of the β-HPV genome per cell in NMSC tumor biopsies. Cell culture, epidemiological, and mouse model experiments support a role for β-HPV infections in the initiation of NMSCs through a “hit and run” mechanism. The virus is hypothesized to act as a cofactor, augmenting the genome destabilizing effects of UV. Supporting this idea, two β-HPV proteins (β-HPV E6 and E7) disrupt the cellular response to UV exposure and other genome destabilizing events by abrogating DNA repair and deregulating cell cycle progression. The aberrant damage response increases the likelihood of oncogenic mutations capable of driving tumorigenesis independent of a sustained β-HPV infection or continued viral protein expression. This review summarizes what is currently known about the deleterious effects of β-HPV on genome maintenance in the context of the virus's putative role in NMSC initiation.